CHILD-FRIENDLY NEIGHBORHOOD PARKS AROUND INDUSTRIAL AREA IN CAKUNG SUB-DISTRICT, EAST JAKARTA, INDONESIA - Nugraha, Ranuna Yonestra; Situmorang, Rahel; Yuslim, Silia (Journal of Synergy Landscape, 2024)
Cakung sub-district in East Jakarta Indonesia has the largest child population aged 0–18 years compared to other sub-districts in East Jakarta. Children need space to play and important for their development. Neighborhood parks developed in residential areas are used as places for children to play. Empirical conditions show that neighborhood parks in the study area are not qualified for the standard of safe distance from industrial activities. The location of industrial activities and mobility poses many safety and health hazards for children. Neighborhood parks as open spaces closest to where children live, can still be a place for children to play. This study aims to identify the quality of neighborhood parks around industrial areas in the Cakung sub-district based on child-friendly criteria. The method used is scoring analysis with the main assessment parameters related to industrial areas and supporting assessment parameters related to the completeness of child-friendly parks, spatial analysis, and quantitative descriptive analysis. The results of this study show that 8 of 16 neighborhood parks do not qualify the criteria for being child-friendly using the main research parameters, the parks are Metland Menteng, PIK, Pulo Indah, Casia, Menteng Asri, Sangkuriang, Yukayuh Metland, and  Cakung Timur. Then the parks are already child-friendly are Buaran Indah,  RW 13 Penggilingan, Penggilingan,  Pulogebang Permai, Modernland,  Cikini Metland, Kenanga Berseri, and Versata Metland. Improving the quality of neighborhood parks around industrial areas can be done with a design approach even though the location of the park is affected by industrial activities